Analisis risiko dalam supply chain proyek konstruksi menggunakan metode supply chain management - Aulia Dewi Ambarsari; Felicia Tria Nuciferani; Mohamad Ferdaus Noor Aulady; Siti Choiriyah; Feri Harianto; Devi Indah Permatasari (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
During the construction process of the Sidoarjo Funeral Home, there were problems related to material flow that eventually caused the work-time to deviate from the planned schedule. This condition indicates the necessary analysis and evaluation of risks that may appear due to material supply chain disruptions. This study aims to identify events and causes of risk in the material supply chain flow using the Supply Chain Operation Reference (SCOR) approach, as well as to formulate and prioritize effective and realistic risk mitigation strategies to improve Supply Chain Management (SCM) performance in the project. After identifying the risks, an analysis of risk causes was conducted, followed by the design of mitigation strategies. The prioritization of mitigation strategies was based on their effectiveness and implementation difficulty. Tshe study identified 19 risk events and 20 risk causes that affected the supply chain flow. Eight mitigation strategies were proposed to address nine dominant risk causes, including developing and implementing SOPs as a communication system, enhancing material security protection, imposing penalties on relevant parties, creating an integrated system, improving coordination and communication with suppliers, establishing agreements with external parties, conducting employee training, and implementing a more rigorous worker selection process.